Pathways of unconventional protein secretion - Nickel, Walter (Current opinion in biotechnology, 2010)
The vast majority of extracellular proteins are secreted by the classical endoplasmic reticulum (ER)/Golgi-dependent pathway, however, numerous exceptions have been identified. Unconventional secretory proteins lack signal peptides and their export from cells is not affected by brefeldin A, an inhibitor of protein transport along the classical secretory pathway. Two general types of unconventional secretion exist. First, export mediated by direct translocation across plasma membranes of cytoplasmic proteins such as fibroblast growth factor 2. Second, export involving intracellular transport intermediates as shown for acyl-CoA binding protein. Here, molecular mechanisms and factors involved in unconventional secretion are discussed with a focus on fibroblast growth factor 2 translocation across plasma membranes and the role of autophagosomes in unconventional secretion of acyl-CoA binding protein.
Gesehen am 30.06.2023